Risk factors for early re‐bleeding and associated hospitalization in patients with colonic diverticular bleeding. (29th August 2013) - Fujino, Y.; Inoue, Y.; Onodera, M.; Kikuchi, S.; Endo, S.; Shozushima, T.; Suzuki, K.
Abstract: Aim: The annual incidence of colonic diverticular bleeding is increasing, but treatments are not yet well established. Here we aimed to identify the risk factors for early re‐bleeding and to determine the associated duration of hospitalization. Method: Records of 90 emergent patients with colonic diverticular bleeding between 1999 and May 2012 were retrospectively reviewed. They were divided into an early re‐bleeding within 1 month group ( n = 24) and a no re‐bleeding group ( n = 66) and we investigated the risk factors for early re‐bleeding. In the former group, we calculated the time from the first haemostasis to early re‐bleeding and the associated duration of hospitalization. Results: Univariate analysis showed that there were significantly more patients with signs of shock ( P = 0.00055) and active bleeding on the first colonoscopy after admission ( P = 0.020) in the early re‐bleeding group. Multivariate conditional logistic regression analysis using stepwise variable selection showed that signs of shock on admission (odds ratio, 5.23; 95% confidence interval, 1.84–14.90; P = 0.0019) remained statistically significant. All patients who re‐bled without signs of shock ( n = 7) and 16 of 17 with signs of shock re‐bled within 126 h (5.25 days) of initial hospitalization. Conclusion: Shock was an independent risk factor for early re‐bleeding. The associated duration of hospitalization was 6 days.